1984
DOI: 10.3109/00016488409130987
|View full text |Cite
|
Sign up to set email alerts
|

The Site of Involvement of Hypertension within the Cochlea:A Comparative Study of Normotensive and Spontaneously Hypertensive Rats

Abstract: The function and morphology of the cochlea of the spontaneously hypertensive rat (SHR) were examined and compared with the age-paired normotensive Wistar Kyoto rat (WKY). Electro- cochleographic study revealed that the function of the cochlea in the SHR declined with increasing age to a greater extent than that of WKY. Electronmicroscopic study revealed that the primary site of the cochlear deterioration of the SHR was the vascular stria, followed by the organ of Corti. Some hypotheses to explain this phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…These rats begin to show elevations in systolic blood pressure at 3 months of age, associated with degeneration in the stria vascularis and elevation in auditory thresholds. [33][34][35] The organ of Corti meanwhile appears to be spared from hypertensive insult. These studies have demonstrated age-related hearing loss in the hypertensive rat beyond that seen in normotensive controls.…”
Section: Discussionmentioning
confidence: 99%
“…These rats begin to show elevations in systolic blood pressure at 3 months of age, associated with degeneration in the stria vascularis and elevation in auditory thresholds. [33][34][35] The organ of Corti meanwhile appears to be spared from hypertensive insult. These studies have demonstrated age-related hearing loss in the hypertensive rat beyond that seen in normotensive controls.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that several tissues behave as end‐organs in small vessel disease. Of these, the retina, heart, kidneys, lungs, and cochlea have been identified thus far 8‐10 …”
Section: Discussionmentioning
confidence: 99%
“…T he negative influence of hypertension on the peripheral, cochlear part of the hearing system is well documented [1][2][3][4][5][6][7][8][9]. However, little is known about the central auditory function in patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%